Pre-university textbooks at the beginning of the 19th century: Grammar, Rhetoric and Philosophy - Roviró-Alemany, Ignasi (Journal of Catalan Intellectual History, 2011)
Over the course of the 19th century, a new field of publishing would appear: that of school textbooks. Although classes had seen textbooks before, it would be over the course of an entire century that they would gain a huge foothold in schools. This article studies the school textbooks of a generation, that of 1817, and focuses on one figure: that of the Catalan thinker Jaume Balmes. Coverage is given to the first textbooks on grammar, rhetoric and philosophy to be used in classes at the Vic Seminary, books that not only allow us to understand the education of said philosopher and the methods of an educational institution, but which also show us the ideological resources of an entire epoch and culture. key words Balmes, school textbooks, rhetoric, philosophy, grammar.